Manufacturing method of organic nanoparticle, and organic nanoparticle
The method addresses the challenge of contamination in nanoparticle production by using a wet bead mill with controlled stirring rotor speed and zirconia beads, achieving efficient and low-contamination nanoparticle production for pharmaceuticals and other applications.
Patent Information
- Application Number
- JP2024185891
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-08-16
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-08-14
AI Technical Summary
Conventional methods for producing organic nanoparticles using wet bead mills face challenges in maintaining processing speed while effectively controlling the contamination from beads and milling members, leading to high concentrations of metal substances in the final product.
A method involving the use of a wet bead mill with a stirring rotor rotating at a specific outer peripheral speed of 7 m/second, using partially stabilized zirconia beads with a size between 0.15 mm to 0.9 mm, and a vertical orientation to minimize contamination by reducing the contact area and wear, thereby producing organic nanoparticles with reduced metal impurities.
The method significantly reduces the contamination concentration of metal substances in the slurry, achieving efficient nanoparticle production with minimal heavy metal impurities, applicable to pharmaceuticals, health foods, and X-ray contrast agents.
Smart Images

Figure 2025013919000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing organic nanoparticles using a wet bead mill, and in particular to a method for producing nanoparticles of poorly soluble pharmaceutical compounds. [Background technology]
[0002] In recent years, attempts have been made to improve the function of health foods and pharmaceutical powders, such as by grinding them to nanometer sizes (nano-grinding). In particular, there have been many attempts to grind drug powders to nano sizes in order to improve the activity of poorly soluble drugs. In addition, by miniaturizing drug particles to nano sizes, there is also the effect of stabilizing the time at which the drug's effectiveness is exerted. Thus, in recent years, research on drugs ground to nano sizes (nano drugs) has progressed and they have been put to practical use.
[0003] Pulverization using a jet mill or a bead mill is a common method for nano-pulverizing organic powders. Among these, pulverization using a wet bead mill is often performed, and is generally carried out as follows. A mixture (slurry) of drug raw material powder and a dispersion medium prepared to a size of several to several tens of micrometers is prepared and supplied to a bead mill containing spherical grinding media (beads). The mixture of the slurry and beads is stirred by the stirring rotor rotating at high speed inside the bead mill, and the drug raw material powder is pulverized. The materials used for the beads include inorganic substances such as zirconia, alumina, hard glass, and silicon carbide, and polymeric materials such as polystyrene and polypropylene.
[0004] Patent Document 1 describes that the size of beads used in nano-pulverization is preferably 3 mm or less, more preferably 1 mm or less, and Patent Document 2 describes that beads of 10 to 1000 micrometers are used to perform the pulverization process to finer particles. Patent Document 3 describes that it is desirable to use beads of less than 500 micrometers in the pulverization process. However, Patent Documents 1 to 3 simply describe the appropriate bead diameter, and do not specifically describe the conditions for the pulverization process.
[0005] Patent Document 4 describes a method of crushing beads of 20 to 200 micrometers by driving a bead mill equipped with a specially shaped stirring rotor so that the peripheral speed of the stirring rotor is 3 to 8 m / sec. However, Patent Document 4 does not describe the mixing of beads and fragments generated from the stirring rotor into the slurry. In the crushing method of Patent Document 4, the use of a specially shaped stirring rotor can improve the crushing efficiency, but the contact area between the beads and the stirring rotor member increases and a high-speed flow is formed locally, which can increase the mixing of beads and fragments of the stirring rotor member into the slurry.
[0006] In the field of pharmaceuticals, generally, the permissible concentration of substances that may be harmful to health is set for drugs, and this also applies to nano drugs. In the grinding process, there is a problem that the components of the beads and mill parts are mixed into the drug as they wear. In the grinding process using a wet bead mill, elements such as zirconium, yttrium, aluminum, silicon, etc., which are components of the beads, and elements such as iron, nickel, chromium, tungsten, etc., which are components of the metal parts of the mill, may be mixed into the drug.
[0007] The concentrations of these elements in the drug substance must comply with the regulatory limit, but because the contaminants are nano-sized, it is preferable to keep the concentrations as low as possible. Patent Document 5 states that in the manufacture of pharmaceuticals, it is desirable to have the amount of heavy metal contamination less than about 10 ppm, but that this is difficult to achieve with a grinding process using beads.
[0008] Patent Document 5 describes the use of beads coated with polymer resin as a grinding medium as a method for reducing the presence of metal substances in nano-sized organic pulverized materials. However, although the presence of metal substances from the beads can be suppressed, there is a risk of the presence of polymer resin. Furthermore, it is possible that metal substances may be mixed in from parts of the bead mill device, but no solution to this problem is described. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Special table 8-501073 [Patent Document 2] Patent Publication No. 2016-84294 [Patent Document 3] Special table 2010-510988 [Patent Document 4] Patent Publication No. 2006-212489 [Patent Document 5] Patent Publication No. 2003-175341 Summary of the Invention [Problem to be solved by the invention]
[0010] Thus, in the conventional nano-pulverization method of organic matter, the only idea was to perform efficient pulverization, and the processing speed was maintained by rotating the stirring rotor at high speed. In addition, although a method for suppressing the inclusion of metal substances was known, as in Patent Document 5, it was necessary to use special beads, and the problem could not be solved with ordinary beads. Moreover, the method described in Patent Document 5 had a risk of contamination with polymer resins, which are coating components of the beads, and heavy metals (chromium, nickel, iron, etc.), which are components of the metal parts of the bead mill device.
[0011] Therefore, a new method was needed for nano-grinding of organic powders using a wet bead mill that could maintain a sufficient processing speed while significantly reducing the concentration of contaminants from the beads and components of the bead mill apparatus. [Means for solving the problem]
[0012] This specification discloses the following: (1) A method for producing organic nanoparticles, comprising the step of stirring, in a container of a wet bead mill, a mixture containing a slurry containing organic particles and beads having an average particle size of 0.15 mm to 0.9 mm with a stirring rotor rotating at a peripheral speed of 7 m / sec or less; (2) A method for producing organic nanoparticles, comprising the step of stirring, in a container of a wet bead mill, a mixture containing a slurry containing organic particles and beads having an average particle size of 0.15 mm or more and a value (mm) or less calculated by 1.07-0.11 x (the peripheral speed of the stirring rotor (m / sec)), with a stirring rotor rotating at a peripheral speed of 7 m / sec or less; (3) The method according to (1) or (2) above, wherein the beads are made of partially stabilized zirconia. (4) The method according to any one of (1) to (3) above, wherein a rotating shaft for rotating the stirring rotor is installed vertically in the container of the wet bead mill. (5) A method for producing organic nanoparticles, comprising a step of stirring a mixture containing beads and a slurry containing organic particles in a container of a wet bead mill with a stirring rotor, the container of the wet bead mill being a vertical cylindrical container having an opening at the top of the cylindrical container, a rotating shaft for rotating the stirring rotor being inserted into the cylindrical container from above through the opening, and the stirring rotor being connected to the rotating shaft; (6) The manufacturing method according to the above (5), wherein a slurry storage tank is provided above the cylindrical container, and the cylindrical container and the slurry storage tank are connected via a connecting pipe line, a rotating shaft for rotating the stirring rotor is inserted into the cylindrical container from above the slurry storage tank via the slurry storage tank and the connecting pipe line, the stirring rotor is connected to the rotating shaft, and the slurry after the bead separation treatment is discharged from the bottom of the cylindrical container; (7) The method according to (5) or (6) above, wherein the stirring rotor rotates at a peripheral speed of 7 m / sec or less. (8) The method according to any one of (5) to (7) above, wherein the beads have an average particle size of 0.15 mm to 0.9 mm. (9) The method according to any one of (5) to (7) above, wherein the average particle size of the beads is 0.15 mm or more and is equal to or less than the value (mm) calculated by 1.07-0.11 x [the peripheral speed of the stirring rotor (m / sec)]. (10) The method according to any one of (5) to (9) above, wherein the beads are made of partially stabilized zirconia; and (11) Organic nanoparticles obtained by the production method according to any one of (1) to (10) above. Effect of the Invention
[0013] The method disclosed herein can reduce contaminants from beads and bead mill parts when pulverizing organic powders such as pharmaceutical compounds into nanoparticles (for example, average particle size of 400 nanometers or less) using a wet bead mill, thereby preventing contamination of the medicine. The method disclosed herein can prevent contamination not only in pharmaceutical products but also in the production of nanoparticles such as health foods and X-ray contrast agents. [Brief description of the drawings]
[0014] [Figure 1] A vertical bead mill that can be used in the method of the present disclosure is equipped with a mechanical seal and discharges slurry from the bottom of a cylindrical container. [Diagram 2] A vertical bead mill that can be used in the method of the present disclosure is equipped with a mechanical seal and discharges slurry from the top of a cylindrical container. [Diagram 3] A vertical bead mill that can be used in the method of the present disclosure is one that is not equipped with a mechanical seal and discharges slurry from the bottom of a cylindrical container. [Figure 4] A horizontal bead mill equipped with a mechanical seal that can be used in the method of the present disclosure. [Diagram 5] This shows the change over time in the average particle size (D50) of organic powder (phenytoin) during grinding. The upper graph shows the results when beads with small particle sizes were used (△: bead diameter 0.1 mm, ◇: bead diameter 0.2 mm, ○: bead diameter 0.3 mm), and the lower graph shows the results when beads with large particle sizes were used (□: bead diameter 0.5 mm, ▲: bead diameter 0.8 mm, ◆: bead diameter 1.0 mm). [Figure 6] The graph shows the change in contaminant concentration (total concentration of zirconium and yttrium in the slurry: ZY concentration (ppm)) over time during the grinding process of organic powder (phenytoin). △: bead diameter 0.1 mm, ◇: bead diameter 0.2 mm, ○: bead diameter 0.3 mm, □: bead diameter 0.5 mm, ▲: bead diameter 0.8 mm, ◆: bead diameter 1.0 mm. [Figure 7] The effect of the peripheral speed of the stirring rotor on the grinding time is shown. ◇: bead diameter 0.2 mm, ○: bead diameter 0.3 mm, △: bead diameter 0.5 mm, ▲: bead diameter 0.8 mm. [Figure 8] The effect of the peripheral speed of the stirring rotor on the concentration of impurities is shown. ◇: Bead diameter 0.2 mm, ○: Bead diameter 0.3 mm, □: Bead diameter 0.5 mm. [Figure 9]The effect of bead diameter on impurity concentration is shown. △: peripheral speed 2 m / sec, ◇: peripheral speed 4 m / sec, ○: peripheral speed 6 m / sec. [Figure 10] The relationship between bead diameter and peripheral speed of the stirring rotor (circumferential velocity) under suitable grinding conditions is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In this specification, the "average particle size" is calculated from the particle size distribution measured by a particle size distribution measuring instrument, and is expressed as the volume-based median diameter (D50). In this disclosure, the value obtained by measurement using HORIBA LA-950 is described as the average particle size. Note that if a static laser diffraction / scattering type particle size analyzer is used, almost the same measurement results can be obtained. Unless otherwise specified, the term "particle size" or "particle diameter" used in this specification has the same meaning as the above-mentioned "average particle size".
[0016] In this specification, the term "slurry" refers to solid organic particles of approximately 100 micrometers or less suspended in a liquid dispersion medium. Generally, a slurry can be prepared using organic particles with an average particle size of 1 to 100 micrometers, but even if the particles are 100 micrometers or more, the method of the present disclosure can be carried out. In the grinding method using a bead mill of the present disclosure, the grinding speed up to a particle size of 5 micrometers or more is extremely fast, and for example, the grinding time from 30 micrometers to 5 micrometers is about 3 minutes, which is extremely short compared to the total grinding time of 45 to 400 minutes. Therefore, the particle size of the organic material before grinding has little effect on the operating conditions of the bead mill. In the present disclosure, the particle size of the organic material particles in the raw material slurry before grinding is preferably 1 to 100 micrometers, but if it is 1 micrometer or more, there is no substantial effect on the setting of the operating conditions.
[0017] The dispersion medium used in the method of the present disclosure is not particularly limited as long as it is a liquid medium in which the organic particles to be pulverized are essentially insoluble, and a person skilled in the art can appropriately select it according to the properties of the organic particles. For example, water or various organic solvents (for example, alcohols such as methanol, ethanol, isopropanol, butanol, ketones such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl isobutyl ketone, ethers such as isopropyl ether, methyl cellosolve, glycol esters such as ethylene glycol, propylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, esters such as ethyl acetate, halogenated hydrocarbons such as methylene chloride and trichloroethane, non-aromatic hydrocarbons such as cyclohexane, aromatic hydrocarbons such as toluene, linear hydrocarbons such as normal hexane, etc.) can be mentioned.
[0018] In this specification, "organic particles" (sometimes referred to as "organic powders" in this specification) may be any solid particles containing an organic compound, and examples thereof include, but are not limited to, any particles of organic compounds used in various fields such as electronic component materials, phosphors, pigments, paints, pharmaceuticals, pesticides, and foods. Organic particles used in the pharmaceutical field include, but are not limited to, pharmaceutical compounds that are active ingredients in pharmaceuticals, additives used in pharmaceutical preparations, and those used in the manufacture of X-ray contrast agents.
[0019] There is no particular limitation on the pharmaceutical compound, and any can be used, including, but not limited to, phenytoin, mefenamic acid, indomethacin, ibuprofen, itraconazole, sulfamethoxazole, probucol, griseofulvin, digoxin, perapamil, tacrolimus, dexamethasone, haloperidol, lamivudine, rebamipide, aripiprazole, risperidone, ketoprofen, flurbiprofen, loxoprofen, felbinac, diferonac, acemetacin, alclofenac, fenbufen, lobenzarit, penicillamine, naproxen, pranoprofen, etodolac, and cyclosporine.
[0020] The concentration of organic particles in the slurry (also referred to as "slurry concentration" in this specification) is not particularly limited as long as it is a concentration that provides fluidity that allows pulverization using a bead mill. In this specification, the slurry concentration is expressed as the weight % of the material to be pulverized (organic particles) relative to the total weight of the slurry. Examples of the slurry concentration used in the method of the present disclosure include any concentration within the ranges of 1 to 70% by weight, 2 to 65% by weight, 3 to 60% by weight, 4 to 55% by weight, and 5 to 50% by weight.
[0021] In this specification, "organic nanoparticles" refers to particles obtained by pulverizing the above-mentioned organic particles to a size of nanometers with an average particle size of less than 1 micrometer, for example, an average particle size of 500 nanometers or less, 400 nanometers or less, 300 nanometers or less, 200 nanometers or less, 100 nanometers or less, 50 nanometers or less, or 20 nanometers or less (also referred to as "nanofracting" in this specification).
[0022] In the method disclosed herein, a stirring rotor fixed to a rotating shaft is rotated in a container of a wet bead mill to stir the mixture of the slurry and beads, thereby pulverizing the organic particles.
[0023] The container of the wet bead mill that can be used in the method of the present disclosure has an inner wall surface that forms a point-symmetric circle with respect to the central axis, and the diameter of the inner wall surface may be constant or may vary in a direction parallel to the central axis. In addition, there may be a portion that is not point-symmetric due to a slurry supply port or the like. The wet bead mill that can be used in the method of the present disclosure stirs a mixture of beads and slurry in a container made of reinforced alumina, silicon carbide, sialon (SiAlON), partially stabilized zirconia, stainless steel, or the like. When it is necessary to suppress the rise in the temperature of the slurry in the container due to friction during the grinding process, the outside of the container may be water-cooled by forming a jacket structure. The capacity of the wet bead mill that can be used in the method of the present disclosure is a capacity that is generally used in the technical field, and is, for example, any capacity from 0.15L to 10L (0.15L, 0.5L, 1L, 2L, 5L, 10L, etc.).
[0024] The stirring rotor may be made of hard ceramics such as reinforced alumina, silicon carbide, sialon, partially stabilized zirconia, etc., with partially stabilized zirconia being preferred.
[0025] By adding calcium oxide or yttrium oxide, cubic zirconia crystals are formed in zirconia, which gives it high strength. Furthermore, by using an amount of additive slightly less than the amount that completely stabilizes the crystals (partial stabilization), the toughness is increased and the ceramic material becomes resistant to wear and breakage. Generally, partially stabilized zirconia contains 4-6 wt% yttrium oxide as an additive to 94-96 wt% zirconium oxide, and further contains other oxides. In this way, partially stabilized zirconia has the advantage of not only being strong, but also having high toughness and being less susceptible to localized defects, so that stirring rotors made of partially stabilized zirconia generate less debris.
[0026] The method of the present disclosure can be carried out using, for example, a wet bead mill apparatus as shown in Figures 1 to 4, but is not limited to these apparatuses and can be carried out using any apparatus commonly used in the art.
[0027] In one embodiment, the bead mill used in the method of the present disclosure is a vertical bead mill (apparatus 1) shown in Fig. 1, in which the slurry is supplied from the top and discharged from the bottom. The container of the bead mill is a vertical cylindrical container with an opening at the top, and a rotating shaft 4 connected to a driving device such as a rotating shaft pulley 9 is inserted vertically into the cylindrical container from above through the opening, and an agitating rotor 5 is connected to the rotating shaft 4. A mechanical seal 13 is installed at the connection between the rotating shaft 4 and the cylindrical container. The slurry flows from top to bottom, and after the beads are separated by a slit-type bead separator 8, it is discharged from the bottom of the cylindrical container.
[0028] In one embodiment, the bead mill used in the method of the present disclosure is a vertical bead mill (apparatus 2) shown in FIG. 2, in which the slurry is supplied from the bottom and discharged from the top. The container of the bead mill is a vertical cylindrical container with an opening at the top of the cylindrical container, and a rotating shaft 4 connected to a driving device such as a rotating shaft pulley 9 is inserted vertically into the cylindrical container from above through the opening. A stirring rotor 5 and a centrifugal bead separator 14 are connected to the rotating shaft 4. Two mechanical seals 13 are installed at the connection part of the cylindrical container. After the beads are separated from the slurry by the centrifugal bead separator 14, the slurry rises in a hollow flow path installed in the rotating shaft and is discharged from the discharge port 7.
[0029] As in the above devices 1 and 2, wet bead mill devices are generally provided with a mechanical seal or a similar sealing device for the purpose of sealing between the rotating shaft and the cylindrical container. Materials for the contact part between the rotating part and the fixed part of the mechanical seal include high-strength metals such as iron, nickel, molybdenum, tungsten, chromium, and silicon, and high-strength ceramics, which may be mixed into the slurry as the sealing device wears during the grinding process in the bead mill. Therefore, the concentration of the contaminants can be further reduced by grinding the organic powder using a bead mill without a sealing device.
[0030] An example of a wet bead mill without a sealing device is one that uses a vertical cylindrical container with a through hole on the top surface of the cylindrical container, a rotating shaft is inserted into the cylindrical container from above through the through hole, and a stirring rotor is connected to the rotating shaft. In the case of a batch type wet bead mill, the device described above is used, but in the case of a circulation type wet bead mill, a mechanism for supplying and discharging the slurry into the cylindrical container without a mechanical seal in the rotating part is required. As one embodiment, an example of such a device is shown in Figure 3.
[0031] The bead mill (apparatus 3) in FIG. 3 has the same structure and capacity as the above-mentioned apparatus 1, but the connection between the rotating shaft and the cylindrical container is open, and is an example of a circulation-type wet bead mill without a sealing device. Above the top cover 2, there is a slurry storage tank 15, and the top cover 2 and the slurry storage tank 15 are connected by a connecting pipe 16. A rotating shaft 4 connected to a driving device such as a rotating shaft pulley 9 is inserted vertically into the cylindrical container via the slurry storage tank 15 and the connecting pipe 16. A stirring rotor 5 is connected to the rotating shaft 4. The slurry flows from the circulation tank 20 through the slurry connecting pipe 22 into the slurry storage tank 15, and further flows into the cylindrical container through the connecting pipe 16. The slurry that has been pulverized while descending in the cylindrical container is separated into beads in a plug-type bead separator 8, and then discharged from the cylindrical container through the slurry outlet 7. The slurry is further returned to the circulation tank 20 through a slurry pipe 18 by a pump 19. To improve slurry flow, a pumping device 17 may be provided on the shaft 4 in the connecting line 16 to push the slurry downwards.
[0032] In addition, other types of bead mills without a sealing device are also applicable to the method of the present disclosure. Examples of other types of bead mills include those with the following structures. A slurry storage tank is located above a cylindrical container, and a through hole is installed connecting the cylindrical container and the slurry storage tank. A rotating shaft extends into the cylindrical container through the through hole and is connected to a stirring rotor at that point. A slurry supply port is located at the bottom of the cylindrical container, and the slurry is crushed while rising. After the beads are separated by a centrifugal bead separator installed at the top of the cylindrical container, the slurry rises through a hollow flow path installed in the rotating shaft and is discharged into the slurry storage tank. The rotating shaft in the through hole has a structure that allows the slurry to flow from the slurry storage tank to the cylindrical container by a circulation pumping mechanism, a slurry swirling blade, etc., as in the device of Figure 3. This flow prevents the beads from leaking through the through hole. The slurry that flows downward through the through hole returns to the slurry storage tank via the centrifugal bead separator and the hollow flow path.
[0033] In the bead mills of the above-mentioned devices 1 to 3, the stirring rotor is equipped with multiple rod-shaped pins, but the stirring rotor may also be equipped with multiple horizontally arranged circular plates arranged in the height direction, or multiple plate-shaped rotors arranged vertically.
[0034] In the method of the present disclosure, since the rotation speed of the stirring rotor is relatively slow, the bead mill used is preferably a vertical bead mill. In the case of a vertical bead mill, centrifugal force acts in a direction perpendicular to gravity, and the force acting on the beads is almost constant in the circumferential direction inside the cylindrical container, so that excessive force does not act locally and the uniformity is high.
[0035] The flow direction of the slurry in the cylindrical container of the bead mill may be either upward or downward, but by flowing the slurry downward, the beads can be packed downward and the frequency of contact between the beads at the bottom of the cylindrical container is improved, so it is more preferable to use a vertical bead mill in which the slurry flows from top to bottom, such as Apparatus 1 or Apparatus 3. However, since the flow speed of the slurry in the vertical direction is low, the difference is small, and the method of the present disclosure can also be carried out using a vertical bead mill in which the slurry flows from bottom to top.
[0036] The method of the present disclosure can also be carried out in a horizontal bead mill. An example of a horizontal bead mill is the bead mill (apparatus 4) shown in Fig. 4. Apparatus 4 has a rotating shaft 4 installed horizontally, and multiple petal-shaped stirring rotors 5 with holes installed parallel to the direction of rotation, which stir the slurry and beads. After the treatment, the slurry is separated from the beads by a screen 23 and then discharged outside the cylindrical container.
[0037] In the case of a horizontal bead mill, the directions of the centrifugal force and gravity are different depending on the circumferential position in the cylindrical container. At the upper part of the side of the cylindrical container, gravity is subtracted from the centrifugal force, so the force pressing the beads is weak. On the other hand, at the lower part, the centrifugal force and gravity are combined, so the force pressing the beads is strong. Since the method of the present disclosure is carried out under conditions where the peripheral speed of the stirring rotor (also referred to as "peripheral speed" in this specification) is relatively slow and the centrifugal force is small, the degree of the above-mentioned phenomenon is large, and the beads are difficult to rise to the top of the cylindrical container, so the processing speed is reduced. For this reason, in the horizontal bead mill, when the peripheral speed is particularly low, the impurity concentration is somewhat increased compared to the vertical bead mill, but it is possible to use the method of the present disclosure.
[0038] In a circulation type wet bead mill, the slurry is generally treated for 3 to 10 minutes per circulation, and the circulation process is generally performed about 5 to 50 times. The general treatment time is 30 to 400 minutes, but it may be shorter or longer depending on the capacity of the mill.
[0039] The beads used in the method of the present disclosure are not particularly limited as long as they are typically used in grinding processes using wet bead mills, and a person skilled in the art can select them appropriately taking into consideration various factors such as the specifications of the bead mill, the characteristics of the material to be ground (e.g., particle hardness, density, particle size, etc.), the desired particle size of the microparticles after grinding, and the viscosity of the slurry.
[0040] Examples of materials for beads used in bead mills include, but are not limited to, glass, alumina, zircon (zirconia-silica ceramics), zirconia, and steel. Zirconia is preferred as a bead material because it has high hardness and tends to be less likely to be mixed with debris due to bead deterioration. In particular, beads made of partially stabilized zirconia are particularly preferred because, as mentioned above, they are not only strong but also have high toughness and are less likely to suffer from localized defects.
[0041] In one embodiment, the method of the present disclosure uses partially stabilized zirconia beads, sometimes referred to herein simply as "beads."
[0042] In this specification, the "bead packing ratio" refers to the apparent volume (volume %) of beads relative to the effective volume of the cylindrical container of the bead mill (the internal volume of the cylindrical container minus the volume of the stirring rotor).
[0043] Those skilled in the art can appropriately select the bead filling rate in consideration of various factors such as the specifications and operating conditions of the bead mill, the viscosity of the slurry, etc. In general, the bead filling rate can be appropriately set within the range of 10 to 95% by volume, for example, within the ranges of 15 to 95% by volume, 25 to 90% by volume, 35 to 90% by volume, 50 to 90% by volume, and 75 to 90% by volume.
[0044] The amount of slurry to be charged into the bead mill can be appropriately selected by those skilled in the art depending on the specifications of the bead mill (for example, the capacity of the grinding chamber of the bead mill used) and operating conditions.
[0045] Generally, organic powders are relatively soft and can be pulverized even with small collision energy of beads, so in the method of the present disclosure, the average particle size of the beads (also referred to as "bead diameter" in this specification) may be relatively small. In addition, the smaller the particle size of the beads, the larger the specific surface area and the faster the pulverization speed. In general, there are two factors in bead wear: wear increase due to the specific surface area of the beads and wear increase due to the mass of the beads. The former is less wear as the particle size of the beads is larger, and the latter is less wear as the particle size of the beads is smaller. Taking both factors into consideration, it is considered that beads of intermediate size are less wear. In the method of the present disclosure, beads having any average particle size within the range of 0.15 mm to 0.9 mm can be used, and for example, commercially available beads with particle size standards of 0.15 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, or 0.9 mm can be used.
[0046] In general, the surface area of the beads is overwhelmingly larger than the surface area of the components of the bead mill. For example, in a bead mill with an effective internal volume of 200 milliliters, the total area of the cylindrical container inner surface and the stirring rotor is 10 5 mm 2 The total surface area of the beads is about 10 6 ~10 7 mm 2 The wear caused by contact between the beads is on the order of 100% and is overwhelmingly greater than the wear caused by the components of the bead mill. Therefore, although the minimum achievable contaminant concentration of the disclosed method for suppressing bead wear varies depending on the shape of the agitator rotor, in principle it can be applied to agitator rotors of all shapes, and the disclosed method can be expected to be effective even for agitator rotors of complex shapes.
[0047] Examples of the stirring rotor of the wet bead mill used in the method of the present disclosure include a stirring rotor in which rod-shaped pins are installed at point-symmetric positions with respect to the direction of rotation, a stirring rotor composed of multiple plates parallel to the direction of rotation, a stirring rotor composed of multiple plates parallel to the direction of the rotation axis, etc. The pin-shaped stirring rotor does not necessarily have to be cylindrical, may be plate-shaped, and does not have to be simply plate-shaped.
[0048] In this specification, "peripheral speed" or "circumferential velocity" refers to the peripheral speed at which the stirring rotor rotates. Under the same bead diameter, the faster the peripheral speed of the stirring rotor, the shorter the processing time. In the method of the present disclosure, a peripheral speed of 1 m / s or more is preferable, but even if the peripheral speed is 0.5 m / s, it is possible to pulverize organic particles to a particle size of about 200 nanometers. The peripheral speed of the stirring rotor also affects the wear of the beads and the stirring rotor parts. In the method of the present disclosure, when the peripheral speed of the stirring rotor is 7 m / sec or less, a sufficient processing speed can be maintained and the concentration of contaminants from the beads and the stirring rotor parts can be significantly reduced. The peripheral speed of the stirring rotor in the method of the present disclosure can be any speed within the range of 0.5 m / sec to 7 m / sec (e.g., 0.5 m / sec, 1 m / sec, 2 m / sec, 3 m / sec, 4 m / sec, 5 m / sec, 6 m / sec, 7 m / sec).
[0049] In one embodiment, the method disclosed herein includes a step of performing a grinding process using partially stabilized zirconia beads having an average particle size of 0.15 mm or more and a value (mm) or less calculated by 1.07-0.11 x (the peripheral speed of the agitator rotor (m / sec)) at a peripheral speed of the agitator rotor of 7 m / sec or less, thereby making it possible to maintain a sufficient grinding process speed and significantly suppress the concentration of contaminants from the beads and the agitator rotor parts.
[0050] In one embodiment, the amount of impurities contained in the organic nanoparticles obtained by the method of the present disclosure is, for example, 0.0001 ppm or more and less than 50 ppm, 0.0001 ppm or more and less than 40 ppm, 0.0001 ppm or more and less than 30 ppm, 0.0001 ppm or more and less than 20 ppm, or 0.0001 ppm or more and less than 10 ppm, based on the total weight of the particles obtained. In this specification, the concentration of impurities is expressed as parts per million (ppm by mass) of the amount of impurities relative to the total mass of the slurry. In addition, in this specification, the "ZY concentration" refers to the sum of the masses of zirconium and yttrium relative to the total mass of the slurry, expressed as parts per million (ppm by mass). In one embodiment, the ZY concentration in the slurry pulverized by the method of the present disclosure is about 5 ppm or less. The concentration of the contaminant in the slurry can be determined by a measurement method commonly used in the art, such as inductively coupled plasma mass spectrometry (ICP-MS).
[0051] In the field of pharmaceuticals, as described in Patent Document 5, it is one guideline to keep the heavy metal concentration in the drug substance at 10 ppm or less, so for example, when the concentration of the slurry to be subjected to the pulverization process is 50% by weight, it is desirable that the heavy metal concentration in the entire pulverized slurry is about 5 ppm or less. However, the present disclosure provides a pulverization method that quickly pulverizes organic powders with a wet bead mill and reduces the concentration of contaminants, and does not necessarily need to satisfy this condition.
[0052] When carrying out the method of the present disclosure, additives can be added to the slurry as necessary. For example, a dispersant can be added to the slurry for the purpose of improving the dispersibility of organic particles in the slurry, preventing aggregation, or stabilizing the dispersed state.
[0053] The dispersant can be appropriately selected in consideration of various factors such as the properties of the organic particles and the dispersion medium, the specifications and operating conditions of the bead mill, etc. Examples of the dispersant include surfactants such as carboxylates (fatty acid salts, etc.), sulfonates (linear alkylbenzenesulfonate sodium, etc.), phosphates (monoalkyl phosphates, etc.), and sulfates (sodium lauryl sulfate, etc.), and polymer compounds such as hydroxypropyl cellulose (HPC), hypromellose (hydroxypropylmethylcellulose (HPMC)), methylcellulose (MC), and polyvinylpyrrolidone (PVP). The amount of the dispersant can be appropriately selected by a person skilled in the art according to a conventional procedure.
[0054] Other grinding conditions necessary for carrying out the method of the present disclosure can be appropriately set by a person skilled in the art taking into consideration various factors (such as the properties of the organic substance, the type of dispersion medium, the viscosity of the slurry, the particle size of the nanoparticles obtained after grinding, and the grinding efficiency).
[0055] The slurry discharged from the bead mill may be dried according to a conventional procedure in the art to remove the dispersion medium, thereby forming a powder containing organic nanoparticles.
[0056] In a further aspect of the present disclosure, there is provided an organic nanoparticle obtainable by the method of the present disclosure. In one embodiment, the organic nanoparticles of the present disclosure comprise a pharmaceutical compound.
[0057] The form of the organic nanoparticles obtained by the method of the present disclosure is not particularly limited, and may be a slurry obtained by the method of the present disclosure, or may be a powder obtained by drying the slurry.
[0058] In a further aspect of the present disclosure, there is provided a composition or material comprising the organic nanoparticles obtained by the method of the present disclosure. Examples of such compositions or materials include electronic component materials such as dielectrics, piezoelectrics, and magnetic materials, phosphors, battery electrode materials, pigments, paints, fine ceramic raw materials, abrasives, pharmaceuticals, agricultural chemicals, and foods.
[0059] In a further aspect of the present disclosure, there is provided a pharmaceutical composition comprising the organic nanoparticles obtainable by the method of the present disclosure.
[0060] The pharmaceutical composition of the present disclosure can be obtained as a final product by using the organic nanoparticles obtained by the method of the present disclosure and undergoing several steps (e.g., granulation, sizing, tableting, coating, etc.) commonly used in the field of pharmaceutical formulations, as appropriate for the desired dosage form.
[0061] As an embodiment, the operation method of the bead mill used in the method of the present disclosure will be described using the device 1 as an example. The slurry is supplied from the slurry supply port 6 into a container consisting of a cylinder 1, an upper cover 2, and a lower cover 3. The mixture of the slurry and the beads is stirred by the stirring rotor 5 connected to the rotating shaft 4. The stirring rotor 5 is made of a plurality of rod-shaped pins. The slurry descends from the slurry supply port 6 in the cylindrical container, generally at a speed of 10 to several tens of mm / sec. The organic particles in the slurry are pulverized by the stirring of the stirring rotor 5. The treated slurry is separated from the beads by a plug-type bead separator 8, and then discharged from the cylindrical container through the slurry discharge port 7. In order to ensure the pressure inside the bead mill, a mechanical seal 13 is installed on the rotating shaft 4. Although not shown in FIG. 1, the discharged slurry flows through a pipe by the pump and returns to the circulation tank. In this way, the slurry is generally treated by circulating between the circulation tank and the bead mill.
[0062] The following experimental and examples further illustrate the present disclosure and should not be construed as limiting its scope in any way. EXAMPLES
[0063] Test Example 1: Effect of bead size on treatment time A wet bead mill (Apex Mill 015 type mill manufactured by Hiroshima Metal & Machinery (corresponding to the above-mentioned "Apparatus 1". In the following test examples and examples, this will be referred to as "Apparatus 1")) was used to grind a slurry (500 g) containing 5% by weight of phenytoin (Shizuoka Caffeine Industrial Co., Ltd., raw material particle size: 16-20 μm), polyvinylpyrrolidone (3% by weight) and sodium lauryl sulfate (0.25% by weight) as dispersants, together with partially stabilized zirconia beads (Nikkato YTZ balls (hereinafter, the same beads were used), bead filling rate: 75%) of various average particle sizes (particle size standards) at a peripheral speed of the stirring rotor of 2 m / sec. Sampling was performed at a predetermined time point during the grinding process, and the particle size of the phenytoin particles and the concentration of impurities (the sum of the concentrations of zirconium and yttrium. In this specification, this will be referred to as "ZY concentration") in the sample were measured. The particle size of the phenytoin particles was measured using an LA-950 (manufactured by Horiba, Ltd.) (the same applies to the following Test Examples and Examples). Measurement conditions: Particle refractive index: 1.610 (phenytoin) Set Zero: 60 seconds Measurement time: 60 seconds Number of measurements: 2 Shape: Non-spherical Solvent refractive index: 1.333 (water) Ultrasonic: None Particle size basis: Volume The concentration of impurities in the slurry was measured according to the following procedure (the same applies to the subsequent test examples and examples). 0.5 g of the ground sample was weighed into a metal-free container, and an internal standard (Co) was added. Then, a mixture of NMP / HCl / HNO3 (90:5:5) was added and dissolved by ultrasonic irradiation to obtain a sample solution. The concentration (ppm by weight) of impurities (zirconium and yttrium) in the sample was measured using an inductively coupled plasma mass spectrometry (ICP-MS) device (iCAPQ (trademark), Thermo Fisher). Measurement conditions: Measured elements: Zr (m / z=90), Y (m / z=89) Nebulizer: Coaxial nebulizer Spray chamber: Cyclone type Spray chamber temperature: constant temperature around 3℃ Injector inner diameter: 1.0mm Sample introduction method: Natural suction High frequency power: 1550W Cooling gas flow rate: 14L / min Auxiliary gas flow rate: 0.8L / min Measurement mode: KED Collision gas: Helium Additive gas: Oxygen Peristaltic pump speed: 20 rpm Integration time: 0.1 seconds Number of times: 3 The results are shown in Figures 5 and 6. The ZY concentration is shown in ppm by mass relative to the weight of the pulverized slurry (hereinafter the same). As shown in Figure 5, when the bead diameter is 0.2 mm or more, the pulverization proceeds quickly until the particle size of phenytoin reaches about 400 nanometers, but when it falls below 400 nanometers, the processing speed decreases and the effect of the bead diameter becomes greater. The smaller the bead diameter, the faster the processing speed, and the time to reach 200 nanometers is shortest for bead diameters of 0.2 mm (◇ in Figure 5) and 0.3 mm (○ in Figure 5). When the bead diameter is 0.1 mm (△ in Figure 5), the initial processing speed is slow and a very small amount of coarse particles of 1 micrometer or more remained, but it was possible to pulverize it to 200 nanometers. As shown above, organic powders are relatively soft, so they can be pulverized even with small diameter beads, which have a small impact energy. In addition, small diameter beads have a large specific surface area, so the processing speed is fast. When the bead diameter is 0.1 mm, the impact force of the beads is small, so it takes time to pulverize powders of tens of micrometers or more, but when the particle size of the powder is 8 micrometers or less, pulverization proceeds rapidly. As shown in Figure 6, data plotting ZY concentration against treatment time showed that good results were obtained when beads with diameters of 0.2 to 0.8 mm were used, with the best results being obtained when beads with a diameter of 0.3 mm (○ in Figure 6). When beads with diameters of 0.1 mm (△ in Figure 6) and 1 mm (◆ in Figure 6) were used, the concentration of impurities (ZY concentration) was high due to bead wear. As mentioned above, there are two factors that cause bead wear: the specific surface area of the beads and the individual mass of the beads. With beads with a diameter of 0.1 mm, the specific surface area had a large effect, leading to greater bead wear, while with beads with a diameter of 1 mm, the mass of each bead was large, leading to greater wear due to the greater collision energy between the beads.
[0064] Test Example 2: Effect of peripheral speed on processing time The relationship between the peripheral speed and processing time in the pulverization process of the present disclosure was investigated. Using the device 1, a slurry (500 g) containing 5 wt % phenytoin (raw material particle size: 16-20 μm), polyvinylpyrrolidone (3 wt %) and sodium lauryl sulfate (0.25 wt %) as dispersants was pulverized to an average particle size of approximately 200 nanometers using partially stabilized zirconia beads (bead filling rate: 75%) with a bead diameter of 0.2 mm to 0.8 mm. The results are shown in FIG. 7. Under the same bead diameter, the higher the peripheral speed, the shorter the processing time. When beads with a diameter of 0.3 mm were used (circle in Figure 7), even at a peripheral speed of 0.5 m / s, it was possible to grind the material to 200 nanometers in about 420 minutes.
[0065] Test Example 3: Effect of peripheral speed on contaminant concentration Using the apparatus 1, a slurry (500 g) containing 5% by weight of phenytoin (raw material particle size: 16-20 μm) and polyvinylpyrrolidone (3% by weight) and sodium lauryl sulfate (0.25% by weight) as dispersants was pulverized to an average particle size of approximately 200 nanometers using partially stabilized zirconia beads (beads filling rate: 75%) in the same manner as in Test Example 2, while changing the peripheral speed of the stirring rotor, and the impurity concentration (ZY concentration) was measured when the average particle size of the phenytoin particles reached 200 nanometers. The results are shown in Figure 8.
[0066] Test Example 4: Effect of bead size on contaminant concentration Using the apparatus 1, a slurry (500 g) containing 5% by weight of phenytoin (raw material particle size: 16-20 μm) and polyvinylpyrrolidone (3% by weight) and sodium lauryl sulfate (0.25% by weight) as dispersants was pulverized to an average particle size of approximately 200 nanometers using partially stabilized zirconia beads (beads packing rate: 75%) of various bead sizes, as in Test Example 2. The peripheral speed of the stirring rotor was set to 2 m / sec, 4 m / sec, and 6 m / sec, respectively, and the impurity concentration (ZY concentration) in the slurry was measured when the average particle size of the phenytoin particles reached 200 nanometers. The results are shown in FIG. 9. The bead diameters used were 0.1 to 1 mm. The ZY concentration at each peripheral speed was lowest for bead diameters of 0.2 to 0.3 mm, and the ZY concentration was high for small and large bead diameters. As shown in Figure 9, the ZY concentration increased rapidly when the peripheral speed was 2 m / s (△ in Figure 9), between bead diameters of 0.8 mm and 1.0 mm, when the peripheral speed was 4 m / s (◇), between bead diameters of 0.5 mm and 0.8 mm, when the peripheral speed was 6 m / s (◯), and between bead diameters of 0.3 mm and 0.5 mm. As shown in Figure 9, for each peripheral speed, the value of the bead diameter at which the ZY concentration reached 5 ppm was obtained from the intersection of the line connecting the data points of the above bead diameters and the horizontal line indicating a ZY concentration of 5 ppm, and the value was recorded. The ZY concentration also increased when the bead diameter was small, and the ZY concentration was higher for a bead diameter of 0.1 mm compared to when the bead diameter was 0.2 mm. Judging from the graph in Fig. 9, the lower limit of the bead diameter at which the ZY concentration exceeds 5 ppm is approximately 0.15 mm. Therefore, the upper limit of the bead diameter at which the ZY concentration increases rapidly is the value affected by the peripheral speed, while the lower limit is about 0.15 mm.
[0067] Test Example 5: Relationship between bead diameter and peripheral speed Using apparatus 1, a slurry (500 g) containing 5% by weight of phenytoin (raw material particle size: 16-20 μm) and polyvinylpyrrolidone (3% by weight) and sodium lauryl sulfate (0.25% by weight) as dispersants was ground at the peripheral speed shown in the table below together with partially stabilized zirconia beads (bead filling rate: 75%) of various bead diameters shown in the table below, and the impurity concentration (ZY concentration) in the slurry when the average particle size of the phenytoin particles reached approximately 200 nanometers was measured. [Table 1] As shown in Figure 10, each data shown in the above table was plotted with the peripheral speed on the horizontal axis and the bead diameter on the vertical axis, and the ZY concentration (unit: ppm) was added to each data point. The upper limit of the bead diameter at which the ZY concentration in the slurry reaches 5 ppm at each peripheral speed (0.87 mm at a peripheral speed of 2 m / s, 0.60 mm at 4 m / s, and 0.43 mm at 6 m / s) obtained from Figure 9 is shown as a circle in Figure 10. As shown in Figure 10, the upper limit of the bead diameter at which the ZY concentration in the slurry reaches 5 ppm (Do) is linearly related to the peripheral speed of the stirring rotor and is expressed by the following formula: Do = 1.07 - 0.11 x [peripheral speed of the stirring rotor (m / sec)] (mm). In addition, the lower limit of the bead diameter at which the ZY concentration in the slurry reaches 5 ppm is about 0.15 mm, as shown in Test Example 4, and is represented by a horizontal line in FIG. As shown in Fig. 10, the ZY concentration in the slurry was suppressed to 5 ppm or less under the conditions where the concentration was distributed within the region between the two straight lines, whereas the ZY concentration increased rapidly under the conditions where the concentration was distributed outside the region between the two straight lines.
[0068] Test Example 6: Effect of Bead Filling Ratio A slurry containing 5% by weight of phenytoin (raw material particle size: 16-20 μm) and polyvinylpyrrolidone (3% by weight) and sodium lauryl sulfate (0.25% by weight) as dispersants was ground using partially stabilized zirconia beads with a diameter of 0.3 mm at various bead filling rates at a peripheral speed of 2 m / sec to an average particle size of approximately 200 nanometers in the same manner as in Test Example 1, and the impurity concentration (ZY concentration) was measured when the average particle size of the phenytoin particles reached 200 nanometers. The treatment time and ZY concentration were 600 min and 0.50 ppm at a filling rate of 25%, 330 min and 0.70 ppm at a filling rate of 35%, 90 min and 0.99 ppm at a filling rate of 75%, and 90 min and 1.4 ppm at a filling rate of 90%. At a filling rate of 25%, the ZY concentration was low but the treatment time was long, and at a filling rate of 90%, the treatment time was the same as at a filling rate of 75%, but the ZY concentration increased slightly.
[0069] Test Example 7: Effect of Slurry Concentration The concentration of phenytoin (raw material particle size: 16-20 μm) in the slurry was changed, and the slurry was pulverized using partially stabilized zirconia beads with a diameter of 0.3 mm (beads packing rate: 75%) at a peripheral speed of 2 m / sec in the same manner as in Test Example 1 using Apparatus 1. The pulverization time required to reach 200 nanometers and the concentration of impurities (ZY) in the slurry at the time of reaching 200 nm are shown in the table below. [Table 2] Even when the phenytoin concentration in the slurry was changed, the grinding time to 200 nanometers did not change much. The ZY concentration also did not change significantly. Thus, at concentrations of 40 wt% or less, the slurry concentration did not affect the ZY concentration. At a high concentration of 50 wt%, the fluidity of the slurry deteriorated, but grinding was still possible.
[0070] Examples 1 to 31 Slurries of various organic particles (phenytoin, sulfamethoxazole, fenofibrate, mefenamic acid, itraconazole) were milled using the bead mills (apparatuses 1 to 4) shown in Figures 1 to 4. The bead mill apparatuses used are as follows (all of the zirconia listed below contains yttrium as an additive). Equipment 1: Apex Mill 015 (manufactured by Hiroshima Metal & Machinery). The materials of the contact parts are tungsten carbide, nickel (mechanical seal), zirconia-reinforced alumina (stator), zirconia (rotor), and perfluoro (O-ring). Equipment 2: Ultra Apex Mill 015 (manufactured by Hiroshima Metal & Machinery). The materials of the contact parts are tungsten carbide, nickel (upper and lower mechanical seal sides), zirconia reinforced alumina (stator), zirconia (separator, rotor), and perfluoro (O-ring). Device 3: Experimental prototype. The materials of the contact parts are zirconia-reinforced alumina (stator), zirconia (rotor), SUS316L (pumping device), and Perfluoro (O-ring). Equipment 4: Dyno Mill Research Lab Type [Small-sized wet dispersion / grinding machine for microbeads] (manufactured by Shinmaru Enterprises). The materials of the contact parts are zirconia (including hafnium) (accelerator, wear bush), SSiC (silicon carbide) (grinding cylinder), nickel, hard chrome plating (screen), and Viton (registered trademark) (O-ring). The conditions and results of the pulverization process for each Example are shown in Table 3. Comparative examples include Comparative Example 1, which used reinforced alumina beads, and Comparative Examples 2 to 6, in which the peripheral speed or bead diameter is outside the range of the conditions of the present disclosure. The impurity concentrations shown are the concentrations of the bead components zirconium and yttrium, the component (aluminum) of the reinforced alumina that is the material of the bead mill container, and the main components of the metal parts used in the bead mill, iron, nickel, chromium, and tungsten (expressed as ppm by mass relative to the weight of the pulverized slurry). [Table 3]
[0071] Examples 1 to 25 show the results of pulverizing 500 grams of slurry to a final particle size of about 200 nanometers using an apparatus 1 with an effective internal volume of 150 milliliters. The ZY concentration in the slurry (the column "ZrY total" in the table) was 5 ppm or less in all cases. The processing time was also within an industrially appropriate range. Even when the slurry concentration was as high as 50% by weight, processing was possible without extending the processing time, and the ZY concentration was low at 1.48 ppm (Example 17).
[0072] Examples 26 and 27 show the results of pulverizing phenytoin in the device 2 having an effective internal volume of 150 mL. In Example 26, the ZY concentration was very low at 0.48 ppm.
[0073] Examples 28 to 30 show the results of treating phenytoin in Apparatus 3, which has a capacity of 150 milliliters and has a mill configuration similar to that of Apparatus 1. In all of the examples, the ZY concentration was low (maximum 1.07 ppm), and the treatment time was within an appropriate range of maximum 300 minutes. Since Apparatus 3 was not provided with a mechanical seal, the concentrations of nickel and tungsten were lower than those in the case of Apparatus 1, which had a mechanical seal (Examples 1 to 25). Thus, the bead mill not provided with a mechanical seal was also found to have the effect of reducing the concentration of heavy metal contaminants in the slurry from metal members.
[0074] Example 31 shows the results of pulverization using Apparatus 4. Apparatus 4 is a horizontal bead mill, and the stirring rotor is an irregularly shaped plate with multiple holes. In terms of processing time, pulverization to 210 nanometers took 70 minutes, which was problem-free. In terms of impurity concentration, the ZY concentration was about 2.1 ppm, which was higher than the concentration when processed using Apparatus 1 under the same operating conditions (about 1.4 ppm in Example 10), but was still a sufficiently good result.
[0075] On the other hand, in Comparative Example 1, in which reinforced alumina beads were used for treatment, the aluminum contamination in the slurry was close to 100 ppm, and the concentration of contaminants was extremely high. This is because reinforced alumina has high strength but low toughness, and therefore wear progresses quickly. Comparative Examples 2 to 6 are examples in which partially stabilized zirconia beads were used in the treatment with the device 1, but the peripheral speed or bead diameter is outside the conditions of the present disclosure (0.15 mm or more and the value (mm) calculated by 1.07-0.11 x [peripheral speed of the stirring rotor (m / sec)] or less). In all of Comparative Examples 2 to 6, the ZY concentration exceeded 5 ppm, with the maximum value being approximately 54.5 ppm. [Industrial Applicability]
[0076] This disclosure can be applied to the production of organic nanoparticles for pharmaceuticals, health foods, X-ray contrast agents, etc. [Explanation of symbols]
[0077] 1. Cylinder 2‥‥Top lid 3‥‥Lower lid 4. Rotation axis 5. Stirring rotor 6. Slurry supply port 7. Slurry discharge port 8. Flag-type bead separator 9. Rotating shaft pulley 10. Belt 11. Motor pulley 12. Motor 13. Mechanical seal 14. Centrifugal bead separator 15. Slurry storage tank 16. Connecting pipes 17. Pumping device 18. Slurry piping 19. Slurry pump 20. Slurry tank 21. Mixing device 22...Slurry connecting pipe 23. Screen
Claims
1. A method for producing organic nanoparticles, comprising a step of stirring, in a container of a wet bead mill, a mixture containing a slurry containing organic particles and beads having an average particle size of 0.15 to 0.9 mm, with a stirring rotor rotating at a peripheral speed of 7 m / sec or less.
2. A method for producing organic nanoparticles, comprising the step of stirring, in a container of a wet bead mill, a mixture containing a slurry containing organic particles and beads having an average particle size of 0.15 mm or more and a value (mm) or less calculated by 1.07-0.11 x (peripheral speed of the stirring rotor (m / sec)), with a stirring rotor rotating at a peripheral speed of 7 m / sec or less.
3. 3. The method according to claim 1, wherein the beads are made of partially stabilized zirconia.
4. The method according to any one of claims 1 to 3, wherein a rotating shaft for rotating the stirring rotor is disposed in a vertical direction within a container of the wet bead mill.
5. A method for producing organic nanoparticles, comprising the step of stirring a mixture containing beads and a slurry containing organic particles in a container of a wet bead mill with a stirring rotor, wherein the container of the wet bead mill is a vertical cylindrical container having an opening at the top of the cylindrical container, a rotating shaft that rotates the stirring rotor is inserted into the cylindrical container from above through the opening, and the stirring rotor is connected to the rotating shaft.
6. 6. The manufacturing method according to claim 5, wherein a slurry storage tank is provided above the cylindrical container, the cylindrical container and the slurry storage tank are connected via a connecting pipeline, a rotating shaft for rotating the stirring rotor is inserted into the cylindrical container from above the slurry storage tank via the slurry storage tank and the connecting pipeline, the stirring rotor is connected to the rotating shaft, and the slurry after the bead separation process is discharged from the bottom of the cylindrical container.
7. The method according to claim 5 or 6, wherein the stirring rotor rotates at a peripheral speed of 7 m / sec or less.
8. The method according to any one of claims 5 to 7, wherein the beads have an average particle size of 0.15 mm to 0.9 mm.
9. The method according to any one of claims 5 to 7, wherein the average particle size of the beads is 0.15 mm or more and is equal to or less than the value (mm) calculated by 1.07-0.11 x [circumferential speed of the stirring rotor (m / sec)].
10. The method according to any one of claims 5 to 9, wherein the beads are made of partially stabilized zirconia.
11. Organic nanoparticles obtained by the method according to any one of claims 1 to 10.
Citation Information
Patent Citations
Grinding method using medium stirring type grinder
JP2006212489A
Bead Mill
JP3222139U
Process for the manufacture of a powder containing lutein
US20140199396A1
Method for producing fine powder and the fine powder produced by the same
US20150258066A1
Fluid energy media mill system and method
US20150343453A1